2020
DOI: 10.1017/ice.2020.390
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) antibodies among healthcare workers with differing levels of coronavirus disease 2019 (COVID-19) patient exposure

Abstract: Healthcare employees were tested for antibodies against SARS-CoV-2. Among 734 employees, the prevalence of SARS-CoV-2 antibodies was 1.6%. Employees with heavy COVID-19 exposure had similar antibody prevalence as those with limited or no exposure. Guidelines for PPE use seem effective for preventing COVID-19 infection in healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 2 publications
(2 reference statements)
7
42
3
1
Order By: Relevance
“…Higher risk of contracting SARS-CoV-2 is reported in several investigations both for HCWs treating [ 16 , [18] , [19] , [20] , 22 ] and not treating Covid-19 patients [ 19 , 22 ], while many other researchers have found no such association [ 25 , 27 , 53 ]. In our data, of those working in ICUs caring for known/suspected COVID-19 patients, only one (0.9%) of the 111 HCWs was CoV(+), consistent with recent research among HCWs in ICUs [ 22 , 26 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk of contracting SARS-CoV-2 is reported in several investigations both for HCWs treating [ 16 , [18] , [19] , [20] , 22 ] and not treating Covid-19 patients [ 19 , 22 ], while many other researchers have found no such association [ 25 , 27 , 53 ]. In our data, of those working in ICUs caring for known/suspected COVID-19 patients, only one (0.9%) of the 111 HCWs was CoV(+), consistent with recent research among HCWs in ICUs [ 22 , 26 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic screening for the seroprevalence of anti-SARS-CoV-2 antibodies is a valuable indicator for the spread of the infection ( Peto, 2020 ). Several recent studies have investigated the prevalence of antibodies specifically directed against SARS-CoV-2 among HCWs with variable findings ( Chen et al, 2020b , Garcia-Basteiro et al, 2020 , Gómez-Ochoa et al, 2020 , Hunter et al, 2020 , Korth et al, 2020 ). A study conducted on 734 HCWs at Indiana University Health, USA revealed 1.6% prevalence rate of SARS-CoV-2 IgG antibodies ( Hunter et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have investigated the prevalence of antibodies specifically directed against SARS-CoV-2 among HCWs with variable findings ( Chen et al, 2020b , Garcia-Basteiro et al, 2020 , Gómez-Ochoa et al, 2020 , Hunter et al, 2020 , Korth et al, 2020 ). A study conducted on 734 HCWs at Indiana University Health, USA revealed 1.6% prevalence rate of SARS-CoV-2 IgG antibodies ( Hunter et al, 2020 ). Similar rate was reported from a study conducted on 316 individuals working in the University Hospital Essen, Germany ( Korth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hunter et al. reported the prevalence of SARS-CoV-2 antibodies among HCWs was 1.6% in Indiana University Health, USA 5 and there was no major difference among groups with different exposure level to COVID-19 patients. Thus they believe their PPE policy is effective to prevent the disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…recently reported the prevalence of SARS-CoV-2 antibodies among HCWs was 1.6% in Indiana University Health, USA. 5 Since the seroprevalence rate had no major difference among groups with different exposure level to COVID-19 patients, they believe their personal protective equipment (PPE) policy is effective to prevent the disease transmission. Thus, we aim to conduct a cross sectional seroprevalence study among HCWs in a tertiary care hospital in Taiwan to evaluate the effect of infection control policy and practice in the hospital setting in Taiwan.…”
Section: Introductionmentioning
confidence: 99%